A preliminary investigation of fixed and repetitive models during object imitation training. Issue 2 (19th November 2019) - Deshais, Meghan A.; Vollmer, Timothy R.
Abstract : Empirically based guidelines for imitation training for children with Autism Spectrum Disorder (ASD) are limited and there is no existing evidence about what types of imitative models foster faster acquisition of imitation in children with ASD. We compared rates of acquisition for two different methods for presenting the imitative model (i.e., repetitive, fixed) in simple (Experiment 1) and conditional (Experiment 2) discrimination arrangements. The results suggest that some children with ASD may acquire imitation more rapidly when repetitive models, rather than fixed models are used to present the target skill. In Experiment 3, we investigated the features of object imitation models that might influence acquisition. The results of Experiment 3 suggest that the dynamic nature of repetitive models might be responsible for the differential acquisition we observed in the earlier two Experiments. Additionally, the presence of an outcome (e.g., stacked blocks) during training does not enhance acquisition.